2019
DOI: 10.1017/s1047951119001665
|View full text |Cite
|
Sign up to set email alerts
|

Development of feeding information for infants with CHD

Abstract: Introduction:Infants with CHD often experience growth failure. Ensuring optimal growth before surgery is associated with improved outcomes and has emerged as a significant cause of parental stress. Parents have reported a perceived lack of accessible feeding information for infants with CHD. To address this gap, the aim of this study was to develop feeding information to better support parents.Materials and methods:A search for existing material on six electronic databases and an internet search for unpublishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…18 Descreveu-se, ainda sobre a importância da Educação em Saúde relacionada ao incentivo da amamentação, por estudo britânico, o desenvolvimento de um material educativo relacionado à alimentação para bebês com CC, sendo o material desenvolvido considerado útil e incluindo informações sobre a jornada de alimentação, outras histórias sobre alimentação infantil e conselhos sobre como aproveitar, ao máximo, o momento da amamentação. 19 Ressaltam-se resultados de sucesso referentes à amamentação de cardiopatas congênitos por grupo do Boston Children's Hospital, que demonstrou que as crianças com CC, após correção da cardiopatia e mantendo a amamentação, demonstraram significativo aumento de peso.…”
Section: Discussionunclassified
“…18 Descreveu-se, ainda sobre a importância da Educação em Saúde relacionada ao incentivo da amamentação, por estudo britânico, o desenvolvimento de um material educativo relacionado à alimentação para bebês com CC, sendo o material desenvolvido considerado útil e incluindo informações sobre a jornada de alimentação, outras histórias sobre alimentação infantil e conselhos sobre como aproveitar, ao máximo, o momento da amamentação. 19 Ressaltam-se resultados de sucesso referentes à amamentação de cardiopatas congênitos por grupo do Boston Children's Hospital, que demonstrou que as crianças com CC, após correção da cardiopatia e mantendo a amamentação, demonstraram significativo aumento de peso.…”
Section: Discussionunclassified
“…13,14 In addition, poor growth and feeding difficulties amongst infants with CHD cause parents significant distress and worry. 15,16 Even in children treated with a structured nutrition pathway, designed to provide intensive nutrition from birth to the time of surgical intervention, 20% remain underweight and 14% remain stunted at the time of surgery. 8 Giallouri et al have previously shown that malnourished children in resource-constrained environments show time-dependent changes in metabolites derived from nutrient-gut microbial-host metabolic interactions, and muscle-associated molecules (energy-and choline-related metabolites).…”
Section: What This Study Addsmentioning
confidence: 99%
“…13,14 In addition, poor growth and feeding difficulties amongst infants with CHD cause parents significant distress and worry. 15,16…”
Section: What This Study Addsmentioning
confidence: 99%